Reconstruction of the High Stigma Exsertion Rate Trait in Rice by Pyramiding Multiple QTLs - Tan, Quanya; Bu, Suhong; Chen, Guodong; Yan, Zhenguang; Chang, Zengyuan; Zhu, Haitao; Yang, Weifeng; Zhan, Penglin; Lin, Shaojun; Xiong, Liang; Chen, Songliang; Liu, Guifu; et al. (Frontiers in Plant Science, 2022)
Asian cultivated rice is a self-pollinating crop, which has already lost some traits of natural outcrossing in the process of domestication. However, male sterility lines (MSLs) need to have strong outcrossing ability to produce hybrid seeds by outcrossing with restorer lines of male parents in hybrid rice seed production. Stigma exsertion rate (SER) is a trait related to outcrossing ability. Reconstruction of the high-SER trait is essential in the MSL breeding of rice. In previous studies, we detected eighteen QTLs for SER from O. sativa, O. glaberrima, and O. glumaepatula using single-segment substitution lines (SSSLs) in the genetic background of Huajingxian 74 (HJX74). In present study, eleven of the QTLs were used to develop pyramiding lines. A total of 29 pyramiding lines with 2- to 6-QTLs were developed from 10 SSSLs carrying QTLs for SER in the HJX74 genetic background. The results showed that the SER increased with increasing QTLs in the pyramiding lines. The SER in the lines with 5-6 QTLs was as high as wild rice with strong outcrossing ability. The epistasis of additive by additive interaction between QTLs in the pyramiding lines was less-than-additive or negative effect. One QTL, qSER3a-sat, showed a minor-effect epistasis, and increased higher SER than other QTLs in pyramiding lines. The detection of epistasis of QTLs on SER uncovered the genetic architecture of SER, which provides a basis for using these QTLs to improve SER level in MSL breeding. The reconstruction of the high-SER trait will help to develop the MSLs with strong outcrossing ability in rice.